2017
DOI: 10.1016/j.brainresbull.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Parkin and PINK1 functions in oxidative stress and neurodegeneration

Abstract: Loss-of-function mutations in the genes encoding Parkin and PINK1 are causally linked to autosomal recessive Parkinson’s disease (PD). Parkin, an E3 ubiquitin ligase, and PINK1, a mitochondrial-targeted kinase, function together in a common pathway to remove dysfunctional mitochondria by autophagy. Presumably, deficiency for Parkin or PINK1 impairs mitochondrial autophagy and thereby increases oxidative stress due to the accumulation of dysfunctional mitochondria that release reactive oxygen species. Parkin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 167 publications
2
88
0
1
Order By: Relevance
“…It has been shown that low cell density increases reactive oxygen species (ROS) in cultured hippocampal NSCs, and that ROS, in turn, increases proliferation but ultimately reduced the growth of NSCs (48). Because several types of PINK1‐deficient cells display increased ROS (49, 50), an ROS‐induced boost of proliferation of PINK1 ‐/‐ NSCs seems a possible mechanism to explain our findings, but further experiments are required to confirm this hypothesis. Regardless of the underlying mechanism, our results show that measuring proliferation of PINK1 ‐/‐ NSCs at a single time point can be misleading and is not useful to judge overall cell growth.…”
Section: Methodsmentioning
confidence: 81%
“…It has been shown that low cell density increases reactive oxygen species (ROS) in cultured hippocampal NSCs, and that ROS, in turn, increases proliferation but ultimately reduced the growth of NSCs (48). Because several types of PINK1‐deficient cells display increased ROS (49, 50), an ROS‐induced boost of proliferation of PINK1 ‐/‐ NSCs seems a possible mechanism to explain our findings, but further experiments are required to confirm this hypothesis. Regardless of the underlying mechanism, our results show that measuring proliferation of PINK1 ‐/‐ NSCs at a single time point can be misleading and is not useful to judge overall cell growth.…”
Section: Methodsmentioning
confidence: 81%
“…As such, the present data suggest that HLA‐mediated proinflammatory processes may be operative in BD rapid cycling. Although such relationship is yet to be objectively proven, a recent study involving a group of rapid cycling BD patients showed the implication of genes involved in cellular oxidative stress and altered mitochondrial functions , two deleterious processes intimately associated with inflammation, specifically in chronic neurodegenerative disorders .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in Parkin and PINK1 were found in PD, which led to their deficient interaction and preventing the clearance of damaged mitochondria via autophagy (15)(16)(17). Normally, Parkin, as an E3 ubiquitin ligase, and PINK1, as a mitochondrially targeted kinase, function together in a common pathway to remove dysfunctional mitochondria by autophagy (18,19). Thus, defects of Parkin or PINK1 can cause not only accumulation of dysfunctional mitochondria and release of reactive oxygen species, but also LB accumulation, including ␣-syn species (11).…”
mentioning
confidence: 99%